'Translators of the old ways': the reinvention of Canadian English in 'Jacob' by Maria Campbell (Métis). Issue 2 (September 2015) - Mongibello, Anna
Abstract : The aim of this article is to highlight the strategies of defamiliarisation of Canadian English adopted by the contemporary Métis writer, Maria Campbell, in her story 'Jacob' (1995). Campbell appropriates and re-maps Canadian English into an 'alterNative' variety that can translate the memories of her nation while retaining traces of the colonial trauma: 'Village English', as the writer defines this new code, constitutes an example of the creative transformation of Canadian English and shows its ability to 'carry' the weight of Indigenous cultural memory.